TYPES OF POLITENESS STRATEGIES IN JOE BIDEN’S CAMPAIGN SPEECH - Kandaga Surya Ardina Pathir; Ruminda; Udayani Permanaludin (Jurnal Sastra - Studi Ilmiah Sastra, 2024)
Politeness is a ways how individuals utilize language to uphold positive social relationships, preserve face, and navigate the intricacies of social interaction. The research aims to explore and understand the politeness strategies employed by Joe Biden in his campaign speeches using the politeness theory proposed by Brown and Levinson (1987). In his campaign speech, Joe Biden employed politeness strategies to foster trust and belief in his words, reflecting a deliberate selection of language in accordance with English rules. Moreover, the perception of politeness may vary across different cultural and environmental contexts. The method used in this research is descriptive qualitative through practical explanation of theory and research through descriptive narratives. The results the study identified a total of 154 instances of politeness strategies, with a predominant use of bald-on-record strategies 66 instances, followed by positive politeness strategies 63 instances. The lesser use of off-record 13 instances and negative politeness strategies 12 instances.